2019
DOI: 10.1126/sciadv.aav3335
|View full text |Cite
|
Sign up to set email alerts
|

In vivo genome editing rescues photoreceptor degeneration via a Cas9/RecA-mediated homology-directed repair pathway

Abstract: Although Cas9-mediated genome editing has been widely used to engineer alleles in animal models of human inherited diseases, very few homology-directed repair (HDR)–based genetic editing systems have been established in postnatal mouse models for effective and lasting phenotypic rescue. Here, we developed an HDR-based Cas9/RecA system to precisely correct Pde6b mutation with increased HDR efficiency in postnatal rodless (rd1) mice, a retinitis pigmentosa (RP) mutant model characterized by photoreceptor degener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 46 publications
0
44
0
Order By: Relevance
“…Cas9 fused to a dominant-negative 53BP1 enhances HDR and inhibits NHEJ in a target-specific manner, without modifying cellular DNA repair mechanisms overall (Jayavaradhan et al, 2019). Efforts have also been made to improve HDR by fusing Cas9 to RecA (RAD51 in eukaryotes), which plays a key role in homologous recombination (Cai et al, 2019;Kurihara et al, 2020), or by altering the conformational checkpoints for Cas9 binding to DNA (Kato-Inui et al, 2018). No product for therapeutic gene editing has yet been approved, but the first clinical trials based on this technology have demonstrated the safety of this approach (Schacker and Seimetz, 2019).…”
Section: Gene Editingmentioning
confidence: 99%
“…Cas9 fused to a dominant-negative 53BP1 enhances HDR and inhibits NHEJ in a target-specific manner, without modifying cellular DNA repair mechanisms overall (Jayavaradhan et al, 2019). Efforts have also been made to improve HDR by fusing Cas9 to RecA (RAD51 in eukaryotes), which plays a key role in homologous recombination (Cai et al, 2019;Kurihara et al, 2020), or by altering the conformational checkpoints for Cas9 binding to DNA (Kato-Inui et al, 2018). No product for therapeutic gene editing has yet been approved, but the first clinical trials based on this technology have demonstrated the safety of this approach (Schacker and Seimetz, 2019).…”
Section: Gene Editingmentioning
confidence: 99%
“…Thus, precise gene editing by HDR (homologydirected repair) may be more desirable, allowing greater control over the editing outcome and correction of a greater range of mutations. The overcome the natural lack the HDR activity in terminally differentiated retinal cells, HDR has been induced in photoreceptors by expressing E.coli recombinase A (RecA) with Cas9 19 (Table 1) A recently developed approach called homology-independent targeted integration (HITI) may further expand the scope of retinal diseases that can be corrected by CRISPR.…”
Section: Classic Crispr-cas9 Based Genome Editingmentioning
confidence: 99%
“…Photoreceptors are responsible for converting light stimuli into electrical stimuli for visual processing. Accordingly, if there is degeneration of these sensory neurons, it will lead to visual loss [ 76 ]. Light and transmission electron microscopic studies showed that hesperitin reduced photoreceptors cell death.…”
Section: Diabetic Retinopathy and The Benefits Of Flavonoidsmentioning
confidence: 99%